The Effect Of The Practicum-based Learning Cycle 5E Learning Model on Critical Thinking Skills on Mechanical Wave Material - Fifi Aprilia; Endang Surahman; Eko Sujarwanto (Universitas Lambung Mangkurat, 2023)
This study aims to determine the effect of learning model learning cycle 5e practicum-based critical thinking skills on mechanical wave material. The low ability of critical thinking is a problem experienced by students of Class XI science, which was the background for researchers to use the 5e learning cycle model based on practicum. This study used a quasi-experimental method with a pretest-posttest design; the sample was determined using a cluster random sampling technique from a population of 180. Testing data using normality test, homogeneity test, and T-test. The findings indicated that t_count = 7.31 and t_table = t ((0.995) (65)) = 2.65. The fact that H_0 is rejected and H_a is approved shows that the practicum-based 5E learning cycle learning model impacts students' critical thinking abilities about mechanical wave content. This is because the value of t_hitung > t_tabel. This is so that students may practice critical thinking skills at various phases of the practicum-based 5E learning cycle learning model. Students get instruction in the fundamentals of clarification at the phases of engagement, investigation, explanation, and elaboration. Students get instruction in inquiry, explanation, elaboration, and assessment as they pertain to the fundamental factors of the choice. Students get instruction in the investigation and explanation phases of the conclusion element. The benefit of this study is that it may serve as a reference for future studies on the impact of the 5E learning cycle's practicum-based learning model on students' critical thinking abilities about mechanical wave content.